2024
DOI: 10.3390/ijms25041982
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Based Skin Regeneration

Zohreh Arabpour,
Farshad Abedi,
Majid Salehi
et al.

Abstract: The skin is subject to damage from the surrounding environment. The repair of skin wounds can be very challenging due to several factors such as severe injuries, concomitant infections, or comorbidities such as diabetes. Different drugs and wound dressings have been used to treat skin wounds. Tissue engineering, a novel therapeutic approach, revolutionized the treatment and regeneration of challenging tissue damage. This field includes the use of synthetic and natural biomaterials that support the growth of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…Hydrogels are particularly effective due to their high-water content and soft tissue-like consistency, which makes them ideal for interacting with the natural skin environment. They promote cell adhesion, proliferation, and migration-all critical for tissue regeneration [19]. Moreover, it has been suggested that biomimetic methods capable of mirroring the structure of the extracellular matrix improve the healing process by offering signals that guide cell behavior and tissue growth [20].…”
Section: Importance Of Skin Regenerationmentioning
confidence: 99%
“…Hydrogels are particularly effective due to their high-water content and soft tissue-like consistency, which makes them ideal for interacting with the natural skin environment. They promote cell adhesion, proliferation, and migration-all critical for tissue regeneration [19]. Moreover, it has been suggested that biomimetic methods capable of mirroring the structure of the extracellular matrix improve the healing process by offering signals that guide cell behavior and tissue growth [20].…”
Section: Importance Of Skin Regenerationmentioning
confidence: 99%
“…Recent studies show promising results for skin tissue regeneration in diabetic and burn wound patients. Polymer-based therapeutic approaches for skin defects using scaffolds made of polymeric materials have become popular in recent years, promoting tissue regeneration [ 1 ]. When skin is injured, proper wound care plays a crucial role in avoiding bacterial infection and accelerating wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hydrogels can be engineered to have therapeutic agent-delivery capabilities, responsive properties, and smart-monitoring abilities, and can serve as delivery vehicles for therapeutic agents such as drugs, cells, and nanoparticles. Stimuli-responsive hydrogels can be used as smart, responsive materials to achieve the on-demand controlled release of loaded active substances [ 1 , 8 ]. The structure and composition of hydrogels closely resemble that of the natural extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regeneration in skin injuries is the second most important but the most frequently addressed problem. Acute skin damage in everyday life is a routine situation, but chronic ulcers in patients with diabetes mellitus, tissue arterial ischemia, varicose veins, and postthrombotic syndrome are a heavy burden on family and state budgets [ 15 , 16 , 17 , 18 ]. Great hopes were pinned on mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%